Abandoning Eugenics and the QALY - Paul C Langley (University of Minnesota Libraries Publishing, 2021)
Should decision making in health care, notably in respect of the allocation of resources between individuals and disease states, rest on notions of the burden of disease and denial of care as assessed by societal evaluations or on the extent to which the need of patients and caregivers is fulfilled. The prospect of the denial of health care, for those deemed 'unworthy' has a long history in the eugenics movement. Many have assumed that this 'utilitarian aberration' has long been discredited. Unfortunately, once the question of the allocation of limited health care resources is considered it reasserts itself; manifested in the creation of health state preferences and states worse than death, and application of the cost-per-QALY calculus driving claims for pricing and access. In the US, this focus on cost-per-QALY claims is most closely associated with the Institute for Clinical and Economic Review (ICER) with its regular clinical assessments and modelled imaginary simulations supporting recommendations which, in many if not most cases, give support to the denial of care. The purpose of this commentary is to point to the unfortunate similarities between 'eugenic' decision making and the application of thresholds in burden of illness cost-per-QALY exercises. If we are to finally rid ourselves of a 'eugenic' approach to health care resource allocation, then we must abandon preferences and the QALY calculus.